1997
DOI: 10.1007/s004240050369
|View full text |Cite
|
Sign up to set email alerts
|

Urea-stimulated K-Cl cotransport in equine red blood cells

Abstract: The effect of urea and its interactions with oxygen tension (PO2), cell volume and inhibitors of protein phosphatases/kinases (PP/PK) on the K influx into equine red blood cells were studied. K influx was measured using 86Rb as a radioactive tracer for K. As in other species, Cl-dependent K influxes were stimulated by urea, with peak fluxes occurring at about 750 mM. This effect was not mediated via changes in cell volume or following formation of cyanate, the hydrolysis product of urea. Stimulation by urea wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…Even though KCC activity is reduced in the hypertonic conditions found in this organ, in equine red cells urea stimulation of KCC is not abolished by hypertonic shrinkage (29). Stimulation of KCC by urea is inhibited by okadaic acid (27) and by calyculin A (21,29), potent inhibitors of PP1 and PP2A (18), indicating that urea stimulation is mediated by phosphorylation/dephosphorylation. Stimulation of KCC by urea could be mediated by inhibition of the KCC inhibitory kinase (12,29).…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Even though KCC activity is reduced in the hypertonic conditions found in this organ, in equine red cells urea stimulation of KCC is not abolished by hypertonic shrinkage (29). Stimulation of KCC by urea is inhibited by okadaic acid (27) and by calyculin A (21,29), potent inhibitors of PP1 and PP2A (18), indicating that urea stimulation is mediated by phosphorylation/dephosphorylation. Stimulation of KCC by urea could be mediated by inhibition of the KCC inhibitory kinase (12,29).…”
mentioning
confidence: 83%
“…Urea activates KCC in dog, human, sheep, and horse erythrocytes (12,21,27,29). It has been postulated that urea may influence dehydration of SS cells pass-ing through the kidney (11,21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…18 Activation is dependent on urea concentration up to 1 M 13,15,16 and is reversible, 13,15 suggesting that protein denaturation is not involved. Gibson et al 14 and Culliford et al 15 first reported stimulation by urea of KCC in SS RBCs and demonstrated its abnormal response to deoxygenation compared with normal cells.…”
Section: Introductionmentioning
confidence: 99%